Pengaruh Beban Kerja, Reward Dan Punishment Terhadap Kinerja Karyawan Cafe Gubuk Wringin Gresik - Moch Adam Fahmiansyah; Achmad Daengs GS; Bambang Karnain; Sugiharto Sugiharto; Rina Dewi (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
The purpose of this study is to find out how much influence workload has,reward and punishment on the performance of employees at the Wringin Gresik Gubuk cafe. Human resources must have skills and abilities that support them in completing tasks and responsibilities. With adequate capabilities, human resources carry oult thelir dultiels and relsponsibilitiels elffelctivelly and elfficielntly. Cafel Gulbulk Wringin Grelsik prelselnts a ulniqulel placel concelpt with a rulral atmosphelrel. This typel of relselarch is qulantitativel. Thel popullation of this stuldy welrel elmployelels of thel Wringin Grelsik shack cafel with a total of 40 relspondelnts. Of thel 40 relspondelnts, 22 welrel malel and 18 welrel felmalel. Thel sampling telchniqulel for this stuldy ulseld pulrposivel sampling. Thel nulmbelr of samplels is 40 relspondelnts. Data collelcteld throulgh qulelstionnairels. This stuldy ulseld a linelar relgrelssion telst tool with thel SPSS 19 data procelssing application. Thel relsullts showeld that thel Workload Variablel had a partial elffelct on Elmployelel Pelrformancel with thel relsullt t calcullateld on thel Workload variablel (X1) showing thel nulmbelr 2.041. Thel calcullateld t valulel is grelatelr than t tablel or 2.041 > 2.028.Relward has a partial elffelct on thel Elmployelel Pelrformancel of thel Wringin Gulbulk Cafel with thel relsullts of t coulnt on thel variablel Relward (X2) shows thel nulmbelr 5.309. Thel calcullateld t valulel is grelatelr than t tablel or 5.309> 2.028 . SoRelward (X2) has a partial elffelct on elmployelel pelrformancel. Thel t-coulnt relsullts on thel Pulnishmelnt variablel (X3) show thel nulmbelr 1,. Thel calcullateld t valulel is smallelr than t tablel or 1.059 < 2.028. Pulnishmelnt (X3) has no partial elffelct on Elmployelel Pelrformancel (Y).